The Potential of Single-Chain Variable Fragment Antibody: Role in Future Therapeutic and Diagnostic Biologics - Getachew Gezehagn Kussia; Tesfaye Sisay Tessema (Journal of Immunology Research)
The advancement of genetic engineering has revolutionized the field of immunology by allowing the utilization of intrinsic antibody structures. One of the biologics that are being produced by recombinant antibody technology is single-chain fragments variable (scFv). Genes of variable regions, the heavy and light chains that are genetically linked into a single transcript by a short flexible linker peptide, are used to generate this fragment from cellular and synthetic libraries. The specificity and affinity of these molecules are comparable to those of parental antibodies. Fusion with marker proteins and other potent molecules improves their stability, circulation half-life, activity, and efficient purification. Besides, this review comprises construction protocols, therapeutics, and diagnostic applications of scFv, as well as related challenges. Nonetheless, there are still issues with efficacy, stability, safety, intracellular administration, and production costs that need to be addressed.